Lesões na córnea: incidência e fatores de risco em centro de terapia intensiva de adultos - Andreza Werli (2010)
Patients in the Intensive Care Unit (ICU) for adults may be at greater risk for injUry to the cornea because, generally, are sedated or comatose, unable to an effective eyelid closure. This type of injury can cause significant damage to the quality of life of patients and difficulty in social reintegration. The aim of this study is to analyze the problem of injury to the cornea in patients admitted to the ICU of a general adult hospital and public education, and specific objectives are: to establish the degree of concordance between the corneal evaluation an intensive care nurse, intensive care physician and an ophthalmologist to estimate the incidence of injuries to the cornea in patients admitted to adult general ICU of a public hospital and education, identify risk factors for developing corneal lesions in patients admitted to a adult general ICU of a public hospital and teaching; propose a model for predicting risk for the development of lesions in the cornea from the selected variables in the Iogistic model. This is a prospective cohort study, conducted from May 2008 to May 2009 in which 254 patients were followed to monitor the development or absence of lesions in the cornea and the risk factors for disease. The data were analyzed using descriptive, univariate and multiple logistic regression. Of the 254 patients enrolled, 59.4% developed lesions in the cornea during the study period, with an average time of onset of injury was 8.9 days. The lesions were punctate-type (55.1%) and corneal ulcers (11 .8%). The final model from the multiple logistic regression analysis, using the method of Forward, included independent variables that predispose a patient to the risk to develop injury to the cornea. The other independent variables remained constant: time of hospitalization until the appearance / regression of the lesion, intubation, mechanical ventilation or tracheostomy; blink less than five times per minute and muscular blocker. The independent variables that predispose to risk injury to the cornea of the punctate type, keeping the other independent variables constant, are: length of hospital stay, another device for ventilatory support, presence of edema and blink less than five times per minute. The independent variables that predispose to risk injury to the cornea-type corneal ulcer, keeping the other independent variables constant, are: Glasgow coma scale and exposure of the eyeball. The study results allow to elaborate a proposal for inclusion of a new nursing diagnosis of Risk for lnjury in the Cornea.